2023
DOI: 10.1590/0034-7167-2022-0717
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the development of children discharged from the Neonatal Intensive Care Unit from parents’ point of view

Lediana Dalla Costa,
Késsia Helen Dalmuth,
Mayeli Thais Fernandes Vieira
et al.

Abstract: Objectives: to analyze the development of children discharged from the Neonatal Intensive Care Unit and how hospitalization interferes with child development, from parents’ point of view. Methods: a descriptive-exploratory, documentary and qualitative study, carried out with parents of children discharged from the Intensive Care Unit through a telephone survey and supplementation in medical records. Data were analyzed using Bardin’s tool and discussed according to scientific evidence. Results: from parents’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Based on the analysis of this study’s results, negative correlations were observed between respiratory rate and/or peripheral oxygen saturation and several inflammatory mediators: IFNg, IL1b, IL2, IL4, IL6, IL10, IL12, IL17, TNF, and VEGF. Such correlations may indicate aspects related to respiratory conditions, a diagnosis often observed in newborns hospitalized in the NICU (Aynalem et al, 2020; Costa et al, 2017; Kim et al, 2018; Rijal & Shrestha, 2018). This trend suggests the need for further investigation into the role of inflammatory mediators in the pathophysiology of these conditions and their potential use as biomarkers for diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 94%
“…Based on the analysis of this study’s results, negative correlations were observed between respiratory rate and/or peripheral oxygen saturation and several inflammatory mediators: IFNg, IL1b, IL2, IL4, IL6, IL10, IL12, IL17, TNF, and VEGF. Such correlations may indicate aspects related to respiratory conditions, a diagnosis often observed in newborns hospitalized in the NICU (Aynalem et al, 2020; Costa et al, 2017; Kim et al, 2018; Rijal & Shrestha, 2018). This trend suggests the need for further investigation into the role of inflammatory mediators in the pathophysiology of these conditions and their potential use as biomarkers for diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 94%